Making Black History Diasporic Fiction in the Moment of Afropolitanism - Haensell, Dominique (Buchreihe der Anglia / Anglia Book Series, 2021)
This study proposes that Afropolitanism may be best approached as a distinct cultural moment or historical constellation that allows us to glimpse the shifting and multiple silhouettes which Africa - as signifier, as real and imagined locus - embodies in the globalized cultural landscape of the 21st century. As such, Making Black History looks at contemporary diasporic fictions that have been written and received in the moment of Afropolitanism.